Management of Inclusive Education Based on Special Classes and Entrepreneurship at Politeknik Negeri Jakarta - Hasyim, Nur; Arifin, Zainal Nur; Katuruni, Innas Rovino; Nurjanah, Darul; Supriatnoko, Supriatnoko (PT Aksara Indo Rajawali, 2025)
The implementation of inclusive education at Politeknik Negeri Jakarta (PNJ) through a special class model based on entrepreneurship has not been thoroughly studied. This research aims to: (i) describe the management of inclusive education at PNJ through a special class model, and (ii) analyze strategies to strengthen students' entrepreneurial capacity. The research employed a descriptive qualitative approach, involving interviews with the Head of the Marketing Management D-3 Study Program for PNJ Special Needs Citizens, observation at PNJ, a literature study, and a documentation study. The data were then analysed qualitatively, including domain analysis, taxonomy analysis, componential analysis, and the drawing of conclusions. The results showed that: (i) the management of inclusive education is carried out through the use of special buildings and classes, with students with special needs grouped based on disability categories - including physical disabilities, sensory disabilities, and intellectual-mental-developmental disabilities, and (ii) strengthening entrepreneurship is carried out through sales practices based on conventional and digital marketing models. This research emphasises the importance of adaptive curriculum development and entrepreneurship integration as part of the strategy to empower students with special needs in higher education.